Third order non-linear optical response of Cu nanoclusters by ion implantation in silicate glass under 532 and 1064 nm laser excitations. (August 2014) - Wang, Y. H.; Liu, F.; Cheng, H.; Yu, X. X.; Wei, L.
Abstract : Metal nanoclusters were produced by ion implantation (Cu + ) in silica glass with dose of 2×10 17 ions/cm 2 . Third order non-linear optical properties of the nanoclusters were measured at 1064 and 532 nm excitations using the Z scan technique. The non-linear refraction index, non-linear absorption coefficient and the real and imaginary parts of the third order non-linear susceptibility were deduced. Results of the investigation of non-linear optical properties by the Z scan configuration are presented, and the mechanisms responsible for the non-linear response are discussed. Third order non-linear susceptibility χ 3 of this kind of sample was determined to be 3·2×10 −7 esu at 532 nm and 1·7×10 −7 esu at 1064 nm respectively.